2023
DOI: 10.1186/s13059-023-02931-y
|View full text |Cite
|
Sign up to set email alerts
|

YY1 lactylation in microglia promotes angiogenesis through transcription activation-mediated upregulation of FGF2

Abstract: Background Ocular neovascularization is a leading cause of blindness. Retinal microglia have been implicated in hypoxia-induced angiogenesis and vasculopathy, but the underlying mechanisms are not entirely clear. Lactylation is a novel lactate-derived posttranslational modification that plays key roles in multiple cellular processes. Since hypoxia in ischemic retinopathy is a precipitating factor for retinal neovascularization, lactylation is very likely to be involved in this process. The pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 85 publications
(31 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…YY1, a transcription factor that regulates gene expression, [ 25 ] undergoes epigenetic modifications implicated in gene mediating. [ 30 , 35 , 36 ] In a study on chronic hepatitis, YY1 degradation via ubiquitination activated the HNF4 α/MiR‐122/CCL2 pathway, [ 35 ] while YY1 phosphorylation at S118 induced atherosclerosis. [ 36 ] Our previous study showed that YY1 lactylation contributed to elevated FGF2 expression.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…YY1, a transcription factor that regulates gene expression, [ 25 ] undergoes epigenetic modifications implicated in gene mediating. [ 30 , 35 , 36 ] In a study on chronic hepatitis, YY1 degradation via ubiquitination activated the HNF4 α/MiR‐122/CCL2 pathway, [ 35 ] while YY1 phosphorylation at S118 induced atherosclerosis. [ 36 ] Our previous study showed that YY1 lactylation contributed to elevated FGF2 expression.…”
Section: Resultsmentioning
confidence: 99%
“…[ 36 ] Our previous study showed that YY1 lactylation contributed to elevated FGF2 expression. [ 30 ] Building on these findings, CUT&Tag analysis was performed to identify the downstream target genes of YY1 lactylation. Briefly, HMC3 cells were divided into two groups: the control group was cultured in serum‐free EMEM and the experimental group was stimulated with LPS+IFN‐γ additionally for 24 h. Using CUT&Tag antibodies against YY1, we identified 29997 overlapped peaks between the two groups ( Figure 7 a ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…19 Thus far, the importance of histone lactylation in facilitating metabolic rewiring, altering the immunological environment, controlling cell destiny and impacting cancer stem-ness and senescence has been discovered (Figure 3 and Table 1). [92][93][94]…”
Section: The Role Of Histone Lactylationmentioning
confidence: 99%